Soft information and the geography of SME bank lending. Issue 4 (3rd April 2021) - Zhao, Tianshu; Luintel, Kul B.; Matthews, Kent
ABSTRACT: This paper explores the geography of bank lending to small and medium-sized enterprises (SMEs) and tests the argument that large institutions with complex organizational structures are better able to filter 'hard' information than 'soft' information. Mortgage lending is used as a control to illustrate the case of 'hard' and 'soft' information. Using data on individual bank lending to SMEs and mortgages by postcode area in Great Britain for the period 2013(2)–2014(4), the paper explains the spatial dispersion of SME lending in the UK in terms of geographical distance and supports the policy of establishing a geographically decentralized financial system as a counterbalance.